This is how I did it, I really hope it helped you with your homework
3(x - 1) = 2x + 9
3x - 3 = 2x + 9
3x (-2x) -3 (+3) = 2x (-2x) + 9 (+9)
(3x -2x) = (9 + 9)
(x) = (18)
x = 18
x = 18 is your answer
hope this helps
Answer:
4
Step-by-step explanation:
2 + 2 = 4
In order to really understand this we need to break it down into simple terms.
Basically what we are doing here is adding two things together.
Put it like this, you have two fish, and you get another two fish, you now have four fish.
If you don't understand anything or need me to explain it better please don't hesitate to ask.
Answer: 4 1/2
Step-by-step explanation:
Answer:
2 x 2 = 4
Step-by-step explanation:
Two cookies plus another two cookies is 4. You can also use a multiplication table. :)